Применение аддитивных технологий для создания дозиметрического фантома головы человека - Поломошнова Д. А. Дарья Анатольевна; Булавская А. А. Ангелина Александровна; Милойчикова И. А. Ирина Алексеевна; Стучебров С. Г. Сергей Геннадьевич (2025, 2025)
Текстовый файл